Determinants of digital technology adoption among rural entrepreneurs in Malaysia - Muhamad Ridwan Jamaludin; Aida Idris (Penerbit Universiti Kebangsaan Malaysia, 2025)
Digital technology could boost a company's ability to compete by enhancing the flexibility of its goods and services. However, a big number of these research studies have been done in urban areas, with limited studies focusing on rural entrepreneurs in Malaysia. A comprehensive literature review was pushed forward to examine the rural market sector, intention to adopt digital technology, and factors that can influence the adoption of digital technology, which eventually could lead to gaining profitable business. Thus, the objective of this study is to determine the factors that can influence rural entrepreneurs’ digital adoption in Malaysia. Two objectives will be achieved: (1) to identify the relationship between perceived usefulness and perceived ease of use towards the intention to adopt digital technology (2) to propose a new framework that integrates the models of TAM and EST in the investigation. A systematic literature review was adopted to classify and evaluate articles using Google Scholar, Social Science Citation Index, and Science Direct. In this literature review, 95 documents were reviewed. Inclusion and exclusion criteria were applied, which reduced the list to 50 articles. The findings of this paper provide a literal idea suggesting that the decision-makers involved in digital adoption must focus on the specific digital technology demands of rural entrepreneurs and the best solution for the business. This paper may only provide an applicable guideline from a theoretical perspective. Future studies suggest using an empirical approach to validate the proposed framework.